CONCEPTUAL SIGNIFICANCE OF INTERTEXTUAL INCLUSIONS WITHIN LITERARY RECIPIENT TEXT (Academia Science Repository, 2023)
In this article are given the notion of allusion and the usage conceptual significance of allusion in literary text.